Very rare congenital malformation: single seminal vesicle, associated with unilateral Kidney Agenesis: first case report - Dan, Mischianu (J Med Life, 2008)
Introduction: The authors present the first case of a patient with single cystic seminal vesicle accompanied by left kidney agenesis, referring for diagnosis and treatment. Material and methods: This is the case of a 22 year old patient presented for chronic pelvic pain. Investigations: abdominal and transrectal ultrasound as well as the computer tomography showed a cystic pelvic tumor with a diameter of around 8,5/6cm, and left kidney agenesis. The treatment for this condition varies from watchful waiting for asymptomatic cysts, to excision. We performed a plasty of the unique seminal vesicle. Results: The postoperative evolution was uneventful with pain remission and improvement of ejaculatory function. Conclusions: Single seminal vesicle has a very low incidence. For this pathology, partial vesiculectomy represents a viable therapeutic option in order to preserve sexual function in the case of a young patient.